Het 123 - A Study Of Language - Pusat Pengajian Ilmu Kemanusiaan, PPIK (Universiti Sains Malaysia, 2007)
UNIVERSITI SAINS MALAYSIA Second Semester Examination Academic Session 2006/2007 April 2007 Het 123 - A Study Of Language Duration : 3 hours